Advanced Python Scripting for Storage Automation - Talluri Durvasulu, Mohan Babu (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
Storage automation is critical for managing the vast amounts of data generated in modern computing environments. Advanced Python scripting offers robust solutions for automating storage tasks, enhancing efficiency, scalability, and reliability. This research explores the utilization of Python's versatile libraries and frameworks to develop automated storage systems. We present a comprehensive methodology encompassing system architecture design, data collection and preprocessing, feature engineering, algorithm selection, and model deployment. The study emphasizes the integration of Python scripts with existing storage infrastructures, enabling real-time transaction verification, sentiment-based escalation triggers, and automated response generation. Through implementation workflows and code examples, we demonstrate the practical applications of Python in automating complex storage operations. Evaluation metrics and continuous monitoring strategies are discussed to ensure system performance and compliance with security standards. The findings indicate that Python-based automation significantly reduces manual intervention, minimizes errors, and optimizes storage management processes. This research contributes to the field by providing a detailed framework for leveraging Python in storage automation, highlighting its advantages, limitations, and potential challenges. Future work will focus on enhancing scalability and integrating machine learning models for predictive storage management.